2001
DOI: 10.1074/jbc.c100035200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Protein Interacts with the Werner's Syndrome Gene Product Physically and Functionally

Abstract: Werner's syndrome (WS) 1 is a rare autosomal recessive disorder characterized by premature aging and an early onset of age-related diseases including arteriosclerosis, malignant neoplasms, melituria, and cataract (1). Somatic cells derived from WS patients show chromosome instability, a shorter life span in in vitro culture, and accelerated telomere shortening (2, 3). WS cells have subtle defects in DNA replication, resulting in a reduced frequency of firing of replication origins (4). In addition, a large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 44 publications
(14 reference statements)
0
90
0
4
Order By: Relevance
“…MGS1 encodes for a DNA-dependent ATPase with ssDNA annealing activities that has been suggested to compete with the PRR pathway for resolution of fork stalling lesions [6,37,38]. RAD30 has been implicated in an error-free form of translesion synthesis [39,40] that some have placed in the PRR pathway [41].…”
Section: Epistasis Analysis Defines a Role For Exo1 In The Mms2 Errormentioning
confidence: 99%
“…MGS1 encodes for a DNA-dependent ATPase with ssDNA annealing activities that has been suggested to compete with the PRR pathway for resolution of fork stalling lesions [6,37,38]. RAD30 has been implicated in an error-free form of translesion synthesis [39,40] that some have placed in the PRR pathway [41].…”
Section: Epistasis Analysis Defines a Role For Exo1 In The Mms2 Errormentioning
confidence: 99%
“…Annotated domains in WRNIP1 include a small Rad18 (radiation-sensitive 18)-like zinc finger at the N terminus and a AAAϩ ATPase domain in the middle of the protein. The homology of WRNIP1 with the replication factor C family of clamp loader proteins, along with its ability to stimulate DNA polymerase ␦ synthesis of new DNA, suggests a possible role for WRNIP1 in replication and/or replication-dependent DNA repair (18,19).…”
mentioning
confidence: 99%
“…10,11) Genetic analyses using MGS1 mutants revealed that Mgs1p is required to prevent genome instability caused by replication arrest and is not involved in the repair of DNA lesions.…”
Section: )mentioning
confidence: 99%
“…15) In this context, it is of note that WRN interacts with Pold 16) and stimulates the DNA synthesizing activity of Pold by increasing the length of synthesized DNA. 17) Since WRNIP1 interacts with WRN, 10,18) WRNIP1 and WRN may interact with templateprimer DNA in a cooperative fashion to regulate the activity of Pold. However, the biochemical relationships between WRNIP1 and WRN at the template-primer DNA remain elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation